Security analysis of encrypted audio based on elliptic curve and hybrid chaotic maps within GFDM modulator in 5G networks - Mohammed Ameen, Mohammed Jabbar; S. Hreshee, Saad (Institute of Advanced Engineering and Science, 2023)
Wireless communications face significant security challenges, so there is an ongoing necessity to develop an appropriate security strategy to protect data from eavesdroppers using cryptography based on chaos theory. Generalized frequency division multiplexing (GFDM) is a modern multicarrier waveform adaptable to 5G requirements, but its security issues have not been considered. Therefore, this paper proposed an efficient security technique within the GFDM modulator to protect the audio transmission against eavesdropping in 5G networks. The proposed GFDM is achieved by separating the subsymbols for the subcarrier into real and imaginary parts and combining them using a mixture of elliptic curve-linear congruential generator sequence (EC-LCG) with Ikeda and Tent maps, respectively. After that, the subsymbols of each subcarrier are permuted independently using the Duffing map. The effectiveness of the proposed approach to resist attacks was tested, and findings that were achieved are histogram, signal to noise ratio (SNR=-27.8068), spectral segment SNR (SSSNR=-34.9912), peak SNR (PSNR=0.9142), frequency weighted log spectral distance (dFWLOG=37.498), cepstral distance (dCD=9.0176), mean square error (MSE=0.82097), keyspace, and speed. These results show that the proposed model provides a high-security level, high speed in the encryption/decryption, large keyspace, and high sensitivity to the initial conditions.